PERAN ASPEK SOSIAL-EKONOMI DAN PEMBIAYAAN SYARIAH TERHADAP USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Nirdukita Ratnawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
MSME's contribution not only to employment, but also to GDP above 50 percent above. This large contribution has not been matched by the ease in generating funds from financial institutions, so the journey of UMKM in increasing the GDP needs to be questioned its optimality, including supported by social and economic aspects. Therefore, further research is intended to reflect the role of Social-Economy and Shari'ah Financing to Gross Domestic Product (GDP) of Micro, Small and Medium Enterprises (MSME) in a circle. In the 2007.1-2016.5 observation period, some variables became proxies for economic and social aspects. The level of variables is the level of Mudharabah and Musyarakah Profit Loss Sharing, the interest rate of Bank Indonesia Sharia Certificates (SBIS) and sharia financing as a proxy of economic aspects. To answer that objective, the analytical tool used is Vector Autoregressive which gives the result (1) on the model of MSME’s GDP in the short term is significantly related by the change of variable of MSMEworkforce since last two months, then there is increasing of accuracy with the increase of manpower and level education, (2) on financing model of SMEs Islamic banks, borne by workers of MSME, PLS mudharabah, PLS musyarakah and high school education in the short term. (4) Result of Impulse Response Function (IRF) shows independent shock variable to MSME PDB variable, non-fluctuate and increasing MSME labor force change to MSME’s GDP, and (5)) The result of Variance Decomposition shows the variability to MSME's GDP by the variability of MSME's GDP, since since the first variability of MSME's GDP has got the work force from MSME's.